2020
DOI: 10.3390/ijms21155189
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Elicits Protective Effects in Intestinal Ischemia Reperfusion Injury

Abstract: Intestinal ischemia reperfusion injury (IRI) is an inherent, unavoidable event of intestinal transplantation, contributing to allograft failure and rejection. The inflammatory state elicited by intestinal IRI is characterized by heightened leukocyte recruitment to the gut, which is amplified by a cross-talk with platelets at the endothelial border. Sulforaphane (SFN), a naturally occurring isothiocyanate, exhibits anti-inflammatory characteristics and has been shown to reduce platelet activation and block leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…It was previously reported that administration of SFN inhibits leukocyte infiltration into tissues [25,30]. This effect may be attributed to the antioxidant and anti-inflammatory properties of SFN, as well as its ability to suppress the expression of vascular endothelial cell adhesion factors, thus suppressing infiltration.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was previously reported that administration of SFN inhibits leukocyte infiltration into tissues [25,30]. This effect may be attributed to the antioxidant and anti-inflammatory properties of SFN, as well as its ability to suppress the expression of vascular endothelial cell adhesion factors, thus suppressing infiltration.…”
Section: Discussionmentioning
confidence: 91%
“…This suggests that Nrf2 may not be involved in phagocytosis. Interestingly, several studies have demonstrated that SFN impacts leukocyte adhesion [30,31]. Based on these observations, it is possible that SFN regulates neutrophil adhesion factors, and thereby inhibits phagocytosis and degranulation by altering adhesion factors.…”
Section: Discussionmentioning
confidence: 99%
“…The current study has several limitations, particularly the lack of a functional assessment of the intestinal graft. It would have been interesting to assess the functional mucosal recovery, with respect to the absorptive and barrier function as altered permeability is a hallmark of intestinal ischemia-reperfusion [41, 44]. In addition, the follow-up time was rather short and does not allow for prognostic considerations related to any of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is a pleiotropic compound with anti-tumor and anti-microbial activities, as widely demonstrated in experimental models [ 231 , 232 , 233 ]. Data obtained in animal models showed a protective activity of sulforaphane in IRI affecting different tissues, including kidney [ 234 ], retina [ 235 ] and intestine [ 236 , 237 ].…”
Section: Nrf2 Signaling Pathway and Ischemic Strokementioning
confidence: 99%